Thin Film TiO2nanorod-PDMS on Glass Substrate for Self-Cleaning Surface - Prayitno, Teguh; Wahyuni, Sri (Universitas Negeri Semarang, 2021)
Self-cleaning is the ability to clean itself on a surface through a hydrophobic mechanism and a photocatalytic mechanism. Self-cleaning properties can be affected by the material used. Titanium dioxide (TiO2) is a material that has photocatalytic properties and Polydimethylsiloxane (PDMS) is a material that is hydrophobic. The aim of this study was to determine the effect of PDMS on the hydrophobic properties of TiO2nanorod-PDMS thin films. TiO2nanorode was synthesized using the solvothermal method. The diffractogram from XRD analysis showed that the synthesized TiO2 was in the anatase phase and the crystallite size was 25.96 nm. TiO2nanonorod-PDMS can be coated on the surface of the glass plate by the spin coating method. The hydrophobic nature of the plate surface is indicated by the contact angle of 126.9Â° at a mole ratio of TiO2 : PDMS 1:2. Its hydrophobic nature contributes to its self-cleaning properties by inhibiting water-containing pollutants. TiO2 contributes to its self-cleaning properties through photocatalytic activity when absorbing UV light and is indicated by the largest decrease in methylene blue levels, which is 92.48% in TiO2nanorod-PDMS glass samples with a ratio of 1:2 and can remove the color of turmeric juice pollutants.